lost star the story of amelia earhart - lauber, patricia (new work scholastic, 1988)
traces the life of the pilot who became the first woman to fly across the atlantic ocean and my steriously disappeared in 1937 while attempting to fly around the world
American corner
include index
11
Keywords: air pilots -- biography; air pilots -- united states; women -- biography